DETERMINING THRESHOLDS OF WATER INDICES TO DETECT SMALL SURFACE WATER AREAS IN WETLANDS OF CHUONG MY DISTRICT, HANOI CITY - Khac Manh, Nguyen; Hai Hoa, Nguyen; Thao Van, Le; Duy Quang, Pham; Dai Nguyen, Vo (Journal of Forestry Science and Technology, 2020)
Developing indicators to monitor changes in surface water areas of wetlands is very crucial with the support of remotely sensing data, which offers to obtain spatial data that is not feasible with in situ measurements. This study aimed to test Sentinel- 2A image suitability for detecting small surface water areas in wetlands using previously published indices. To obtain this objective, the study used the medium spatial resoluton Sentinel-2A image, covering 32 townships and communes of Chuong My district. To validate the results, 460 GPS points in total (360 points in water areas, 100 points in land areas) were distributed randomly within a 10 m buffer around the border of each digitised water polygon. These polygons were mapped using as a base map Goolge Earth image. As a result, the best performing index was the NDWI with accuracy of 90.0%, followed by 89.7% and 89.4% for MNDWI and B_BLUE, respectively. Overall accuracy and Kappa index results were optimal for -0.35 threshold for NDWI (0.80 for Kappa coefficient) and MNDWI (0.79 for Kappa coefficient) in Chuong My district. Therefore, using Sentinel-2A image to calculate the NDWI and other indices to monitor flooded areas and changes in surface water areas is suitable in Chuong My district.